Molecular detection of Toxoplasma gondii and Neospora caninum in neotropical primates. Issue 3 (12th March 2022) - Cândido, Stéfhano Luís; Fonseca, Maria Julia de Oliveira Rosa; Pacheco, Richard de Campos; Campos, Camila Gonçalves de; Morgado, Thais Oliveira; Colodel, Edson Moleta; Nakazato, Luciano; Dutra, Valéria
Abstract: Background: Toxoplasma gondii and Neospora caninum infections in primates are potentially fatal and directly impact the conservation of these animals and public health. Materials and methods: A total of 38 blood/clot samples collected from free‐living and captive neotropical primates undergoing clinical care or found dead by environmental authorities in the Mato Grosso State, Brazil, were analyzed by PCR for DNA detection of T . gondii and N . caninum . Furthermore, eight animals were submitted to immunohistochemistry for the detection of T . gondii . Results: DNA of T . gondii and N . caninum was amplified in 11 (28.95%) 10 (26.32%) of samples analyzed, respectively. Coinfection was observed in three individuals. One animal returned a positive result in the immunohistochemistry for the detection of T . gondii . Conclusion: These findings reflect a concern for the conservation of these animals, as the pathogen–host interaction is unpredictable and infections by these protozoa can lead to animal mortality, which has a substantial impact on endangered species.